Hubungan Pemeliharaan Hewan Ternak Dengan Prevalensi Kasus Malaria - Rangga Sakti Budi Putra (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2019)
Malaria is a life threatening disease that are wide spread and has long-term effect upon living and economical quality of it’s patients. Infection is caused by the bite of Anopheles mosquito which is the vector of Plasmodium parasite. Animals has the role of diverting mosquito bite from humans, so it may deny the transmission of parasite to human (zooprophylaxis). Animals, in this case, cattles, may also increase the chance of mosquito as a vector to continously breed and increases malaria transmission (zoopotentation). Studies has been conducted on different villages and shows the positive relation between ownership of cattles and parasite rate, thus making ownership of cattles increases the probability of malaria transmission.